2016
DOI: 10.1080/00016357.2016.1193625
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maxillary lateral incisor agenesis and associated skeletal characteristics in an orthodontic patient population

Abstract: Patients with maxillary lateral incisor agenesis showed a significant tendency for skeletal Class III compared with the Class I control. This could be attributed to maxillary hypoplasia/retrognathia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
2
21
0
6
Order By: Relevance
“…Some previous studies have reported an association between TA and craniofacial morphological patterns [16][17][18][19][20][21][22][23], including retrognathic maxilla [18], class III skeletal malocclusion [18,22], and concave profile [21]. Additionally, our recent study demonstrated that TAassociated GLI2 and GLI3 genes might play a role in the development of skeletal malocclusions [24].…”
Section: Introductionsupporting
confidence: 55%
“…Some previous studies have reported an association between TA and craniofacial morphological patterns [16][17][18][19][20][21][22][23], including retrognathic maxilla [18], class III skeletal malocclusion [18,22], and concave profile [21]. Additionally, our recent study demonstrated that TAassociated GLI2 and GLI3 genes might play a role in the development of skeletal malocclusions [24].…”
Section: Introductionsupporting
confidence: 55%
“…However, MLIA did not cor relate with the change in the inclination of the palatal plane relative to the Frankfurt plane. A study by Bas siouny et al [35] showed that patients with congeni tal lack of maxillary lateral incisors have a significant tendency to skeletal class III. The researchers attribute these results to the occurrence of maxillary hypoplasia (retrognathia) in these patients.…”
Section: Analysis Of the Obtained Resultsmentioning
confidence: 99%
“…Patients with an Class I malocclusion with mandibular crowding requiring extractions, and those with a Class II malocclusion with a mildly convex profile may be successfully treated with space closure, but those whose profiles are moderately to severely convex, with a retrusive mandible, and a deficient chin prominence may require treatment that also addresses the facial profile . An orthodontic population examined by Bassiouny et al, demonstrated a significant tendency toward a skeletal Class III relationship in patients with missing laterals and space closure may exacerbate this discrepancy. Restoration with a RBFDP or an implant may be a better option for these patients.…”
Section: Canine Substitutionmentioning
confidence: 99%